Myeloid cell nuclear differentiation antigen controls the pathogen-stimulated type I interferon cascade in human monocytes by transcriptional regulation of IRF7. - Bowie, Andrew; Bracken, Adrian; Brady, Gareth (My University, 2022)
Type I interferons (IFNs) are critical for anti-viral responses, and also drive autoimmunity when dysregulated. Upon viral sensing, monocytes elicit a sequential cascade of IFNβ and IFNα production involving feedback amplification, but how exactly this cascade is regulated in human cells is incompletely understood. Here we show that the PYHIN protein myeloid cell nuclear differentiation antigen (MNDA) is required for IFNα induction in monocytes. Unlike other PYHINs, this is not due to a pathogen sensing role, but rather MNDA regulated expression of IRF7, a transcription factor essential for IFNα induction. Mechanistically, MNDA is required for recruitment of STAT2 and RNA polymerase II to the IRF7 gene promoter, and in fact MNDA is itself recruited to the IRF7 promoter after type I IFN stimulation. These data implicate MNDA as a critical regulator of the type I IFN cascade in human myeloid cells and reveal a new role for human PYHINs in innate immune gene induction.
PUBLISHED
Keywords: interferons (IFNs); RNA polymerase II; antigen (MNDA)